Phytoremediation of Coal Mine Acid Drainage Using the Invasive Weed Cyperus rotundus and Typha angustifolia: Optimizing Biomass Density in a Substrate-Free Batch System - Rinda Rahmadhani; Muhammad Mahfuzh Huda; Rabiatul Adawiyah; Jevon Ona Ivena (Tecno Scientifica Publishing, 2026)
Acid mine drainage (AMD) presents a persistent environmental challenge, particularly in tropical mining regions. This study evaluated the phytoremediation potential of the zero-cost invasive weed Cyperus rotundus against the established hyperaccumulator Typha angustifolia in a substrate-free batch system. Utilizing extreme raw AMD (pH 2.69; Fe 6.40 ppm; TDS 1,390 ppm), the experiment encompassed a baseline comparison (9 clumps), density optimization (6–15 clumps), and a synergistic mixed-culture evaluation over 15 days. Baseline results indicated that T. angustifolia intrinsically outperformed C. rotundus in iron (Fe) removal (89.10% vs. 82.22%) by day 10. However, optimizing C. rotundus to a 15-clump saturation threshold successfully overcame this deficit, achieving 91.20% Fe attenuation (0.56 ppm). Crucially, extended hydraulic retention (15 days) in high-density configurations induced a severe secondary pollution event, catastrophically increasing Total Dissolved Solids (TDS) to 2,300 ppm because of biomass carrying capacity limits and necrosis. The mixed-culture configuration exhibited the highest overall efficacy, maximizing Fe removal (92.63%), buffering pH to 3.27, and moderating late-stage TDS spikes. The findings demonstrated that while C. rotundus was a highly viable bioremediator, engineering designs needed to cap biomass at the saturation threshold and strictly enforce a 6- to 10-day retention window to prevent secondary decay pollution.